The Financial Costs of the U.S.-China Trade Tensions Evidence from East Asian Stock Markets - De Nicola, Francesca (World Bank E-Library Archive, 2019)
This paper examines the impacts of U.S.-China trade tensions via the lens of East Asian stock markets. Studying 10 indices of the main East Asian stock markets, it finds that announcements of "trade war" escalation translated into 50 to 60 percent of the total declines in two major Chinese stock markets over the first eight months of 2018. In other words, in the absence of the "trade war" Asian stocks would have experienced half the decline, or they would have registered gains